Daisy Burns (Volume 1) - Kavanagh, Julia, 1824-1877 (Salt Lake City, UT : Project Gutenberg, 2011)
"Daisy Burns (Volume 1)" by Julia Kavanagh is a novel written in the mid-19th century. The story centers around a young girl named Margaret Burns, who lives in solitude with her father, a physician, in a remote cottage. The narrative unfolds her experiences, emotions, and interactions as she navigates childhood innocence amidst loss and change. At the start of the book, we find Margaret deeply affected by her father's death, which leads her to reflect on her past and her current state of isolation. As she struggles with feelings of grief and jealousy over her father's friendship with Cornelius O'Reilly, a visiting family friend, Margaret's character emerges as both proud and sensitive. The opening portrays a poignant blend of nostalgia and sorrow, illustrating her struggle to cope with her new reality. It sets the foundation for her future interactions as she transitions from her sheltered upbringing to the complexities of a broader world, signified by her eventual connection to Cornelius and the anticipation of life beyond the confines of her father's cottage. (This is an automatically generated summary.)
Release date is 2011-05-18
Keywords: Orphans -- Fiction; Guardian and ward -- Fiction; England -- Social life and customs -- Fiction